Analisis perbandingan visi misi, SWOT, dan tujuan jangka panjang Baitul maal wat Tamwil di Indonesia - Ramadhan, Alkhawarizi Surya; Rozikin, Mochammad Ainur; Febriyansah, Dimas Almadani (Maliki Interdisciplinary Journal, 2024)
Baitul Maal wat Tamwil is a financial institution with a sharia concept that was born as an option that combines the concepts of grinding and taming into one institutional activity. In addition, Baitul mal wa tamwil (BMT) has become an important part of economic growth in Indonesia. With the aim of collecting public funds and functioning as an alternative for micro business development, BMT maslahah is able to provide financing for micro business empowerment. This study aims to compare the strategic planning of the three BMTs in Indonesia, namely BMT Maslahah, BMT Salsabila and BMT Bahtera by comparing the vision and mission of each company, the company's long-term goals and SWOT analysis of each company. In terms of vision and mission, the results show that the three BMTs have a vision that is not much different, namely wanting to improve the welfare of members and their communities. In terms of longterm goals, these three BMTs have the same goal of providing sharia services and products to the community and developing the community's economy and in the SWOT analysis, each of the three BMTs has different strengths, weaknesses, opportunities, and threats.